Symbolic Violence against Women in Cho Nam Joo’s Kim Ji Young Born 1982 - Agita Nurul Arofah; Ali Mustofa (Hasanuddin University, 2022)
This study aims to identify the forms of symbolic violence experienced by the character named Kim Jiyoung and other female characters in the Kim Jiyoung Born 1982 novel by Cho Nam Joo using symbolic violence theory in the mechanism of euphemism and censorship. Euphemism is a mechanism by hiding the intent of violence that works subtly and unconsciously. Meanwhile, censorship is a mechanism that makes symbolic violence a value preserved and considered absolute. This study employed a descriptive qualitative method to understand the symbolic violence phenomenon contained in the novel. The data collection technique was carried out using close reading technique. The data were taken from dialogue and narrations related to the symbolic violence issues. The results of this study revealed that the symbolic violence experienced by Kim Jiyoung and other female characters occurs in the domestic and public sphere. The euphemism mechanisms showed that symbolic violence occurs through concern, labeling, insistence, prohibition, subtle rejection, belief, and giving permission. Meanwhile, censorships were in the form of marginalization in culture, women's role, generosity, and unequal division of labor.